Semi-activated oscillating hydrofoil as a nearshore biomimetic energy system in waves and currents. (15th April 2018) - Filippas, E.S.; Gerostathis, Th.P.; Belibassakis, K.A.
Abstract: The performance of oscillating hydrofoils in the presence of waves and currents is studied for the exploitation of combined renewable marine energy sources in nearshore and coastal regions. The system operates as a semi-activated biomimetic energy device, with imposed pitching motion and induced heaving motion in harmonic incident waves and flow. Except of uniform currents also vertically sheared currents are considered. The analysis is based on a Coupled-Mode System, in conjunction with a time-domain BEM, taking into account the effect of the wavy free surface, the velocity due to waves and currents on the formation of the incident flow, and the effects of variable bathymetry. Results are presented concerning the performance of the system for a wide range of parameters, including cases where the wave frequency is different from the pitching frequency of the hydrofoil. It is indicated that significant energy can be extracted, and that the power gain from the waves increases well above the maximum values predicted for the system in uniform flow. The present method can be applied to the design and optimum control of such biomimetic systems operating in the nearshore/coastal region and extracting energy from waves in the presence of ambient currents. Highlights: Performance of oscillating hydrofoils as biomimetic energy systems in nearshore and coastal regions. Wave-current-seabed effects in the presence of variable bathymetry and vertically sheared inhomogeneous current. Hybrid coupled mode – time domain Boundary Element Method. Combined wave-current extracted power and operability characteristics of the system for wide range of parameters.